Asynchronous forum discussion as a tool on the teaching of business: a study on a statistics applied to business discipline - Mantovani, Daielly Melina Nassif; Gouvêa, Maria Aparecida; Viana, Adriana Backx Noronha (Revista de Administração da UFSM, 2017)
This article aims to assess the use of forum tool on the teaching of Statistics Applied to Administration. For this purpose, a case study has been done, with descriptive treatment of data, which focused on an interaction through a forum, occurred on a blended discipline. The forum intended to bring the Statistic´s theoretical concepts and the real use of them on business field. That interaction consisted of discussion of scientific paper which had used the Analysis of Variance (ANOVA) on its data analysis. Most of the messages posted by the students were considered correct and relevant, defining a deep discussion. However, there was a high level of repetition, many messages were posted on the last day of the activity and the forum was lowly accessed after its conclusion as a research source. We´ve observed that daytime students participated more adequately than nocturnal students, posting a higher quantity of new and deep messages. Forum discussion tool can be used in education, but it needs a previous planning and anticipation of possible problems, developing actions to correct them.